2020
DOI: 10.1111/evo.13943
|View full text |Cite
|
Sign up to set email alerts
|

Birds rarely hybridize: A citizen science approach to estimating rates of hybridization in the wild*

Abstract: The rate of hybridization among taxa is a central consideration in any discussion of speciation, but rates of hybridization are difficult to estimate in most wild populations of animals. We used a successful citizen science dataset, eBird, to estimate the rates of hybridization for wild birds in the United States. We calculated the frequency at which hybrid individuals belonging to different species, families, and orders of birds were observed. Between 1 January 2010 and 31 December 2018, a total of 334,770,19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
79
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(86 citation statements)
references
References 39 publications
4
79
3
Order By: Relevance
“…Hybridization refers to the situation where species "that are distinguishable on the basis of one or more heritable characters overlap spatially and temporally and cross to form viable and at least partially fertile offspring" (Arnold 1997). Although this phenomenon is rare on an individual level, hybrids between numerous bird species have been documented (Justyn et al 2020;Ottenburghs and Slager 2020). Indeed, according to the latest estimates, about 16% of bird species has hybridized with another species (Ottenburghs et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Hybridization refers to the situation where species "that are distinguishable on the basis of one or more heritable characters overlap spatially and temporally and cross to form viable and at least partially fertile offspring" (Arnold 1997). Although this phenomenon is rare on an individual level, hybrids between numerous bird species have been documented (Justyn et al 2020;Ottenburghs and Slager 2020). Indeed, according to the latest estimates, about 16% of bird species has hybridized with another species (Ottenburghs et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In this issue, Justyn et al. (2020) provide the first data‐based estimate of individual hybridization rate in birds using data from the citizen science project eBird.…”
mentioning
confidence: 99%
“…Grava et al (2012) noted all of the admixed chickadees identified in their study were phenotypically mountain chickadees. Justyn et al (2020) used phenotypic analysis only and these results combined with our own suggest that rates of hybridization may be higher than currently estimated as hybrids are not always phenotypically distinguishable or easy to detect based on phenotype alone (Ottenburghs and Slager 2020).…”
Section: Discussionmentioning
confidence: 81%
“…We documented admixture among five of the six chickadee species pairs examined; we did not detect any admixture between mountain and chestnut‐backed chickadees. The prevalence of admixture among chickadee species is not surprising given Justyn et al (2020) found that among passerines, hybridization is most frequent in family Paridae. mountain × black‐capped chickadee and boreal × black‐capped chickadee hybrids were previously documented by Grava et al (2012) and Lait et al (2012), but our study provides genetic evidence to suggest admixture occurs between black‐capped × chestnut‐backed, boreal × chestnut‐backed and boreal × mountain chickadees and admixture rates vary based on geographic location.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation